Evaluation of clinical and radiographic measures and reliability of the quadriceps angle measurement in elderly women with knee osteoarthritis - Mateus Ramos Amorim; Sueli Ferreira da Fonseca; Arthur Nascimento Arrieiro; Wellington Fabiano Gomes; Ana Cristina Rodrigues Lacerda
Introduction Knees osteoarthritis (OA) is a complex degenerative disease with intra-articular changes affecting the amplitude of the quadriceps angle (Q). To measure this variable, it is necessary to use reliable protocols aiming at methodological reproducibility. The objective was to evaluate the intra-examiner and inter-examiner reliability of clinical and radiographic measures of the Q angle and to investigate the relationship between the degree of OA and the magnitude of this angle in the elderly. Materials and methods 23 volunteers had the Q angle measured by two evaluators at 48-h interval. Clinical measurements were collected by using the universal goniometer in the same position adopted in the radiographic examination. Results The intra-examiner reliability was good (0.722 to 0.763) for radiographic measurements and low (0.518 to 0.574) for clinical assessment, while inter-examiner reliability was moderate (0.634) for radiographic measurements and low (0.499) to the clinics. The correlation analysis between the radiographic values with the OA classification showed no correlation between them (p = 0.824 and r = -0.024). Conclusion Clinically, it is suggested that the radiographic examination is preferable to evaluate the Q angle of elderly women with knee osteoarthritis. Moreover, the magnitude of this angle did not correlate with the degree of impairment of OA in this population.